A Randomized Clinical Trial Comparing Family-Focused Treatment and Individual Supportive Therapy for Depression in Childhood and Early Adolescence - Tompson, Martha C. (J Am Acad Child Adolesc Psychiatry, 2017)
OBJECTIVE: Despite the morbidity and negative outcomes associated with early-onset depression, few studies have examined the efficacy of psychosocial treatment for depressive disorders during childhood. Integrating family in treatment may have particularly salutary effects during this developmental period. This trial compared immediate posttreatment impacts of family-focused treatment for childhood depression (FFT-CD) and individual supportive psychotherapy (IP) for children aged 7–14 years with depressive disorders. METHOD: Children were randomized to 15 sessions of FFT-CD (n = 67) or IP (n = 67) over 4 months. The primary treatment outcome was adequate clinical depression response, defined as a ≥50% reduction on the Children’s Depression Rating Scale-Revised (CDRS-R). Additional outcomes included patient-centered outcomes (parent- and child-reported treatment satisfaction), remission (defined as CDRS-R ≤ 28), change on continuous CDRS-R score, and change on child and parent reports of depressive and non-depressive symptoms and social adjustment. RESULTS: Significant improvement was evident across groups on depressive and non-depressive symptoms, global response, and functioning/social adjustment. Compared to children randomized to IP, children randomized to FFT-CD showed higher rates of adequate clinical depression response (77.7% vs. 59.9%, number needed to treat = 5.72, OR = 2.29, 95% CI [1.001, 5.247], t = 1.97, p = .0498). Across treatments families reported high satisfaction; relative to IP families, FFT-CD families reported greater knowledge and skills for managing depression. There were no significant differences between treatment arms on secondary outcomes. CONCLUSION: Results support the value of psychosocial intervention, underscore the important role families play, and highlight the potential for FFT-CD for supporting recovery among children suffering from depression.